1999
DOI: 10.1046/j.1440-0960.1999.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Crusted scabies in two immunocompromised children: Successful treatment with oral ivermectin

Abstract: Two immunodeficient children, aged 4 and 12 years, with crusted scabies were successfully treated with a single oral dose of ivermectin (200 micrograms/kg). One child had been diagnosed in infancy with an undefined congenital T cell immunodeficiency and the other with chronic mucocutaneous candidiasis. Both had failed to respond to conventional topical therapy. In view of the excellent therapeutic response and absence of side-effects, ivermectin should be considered in the treatment of recalcitrant crusted sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…The mange described in the juvenile gorilla in the present study was clinically very similar to classical crusted scabies in children (Burgess 1994;Patel et al 1999;Gladstone and Darmstadt 2000), including reports from this region of Africa (Schmeller 1998;Henderson and Nykia 1992;Heyndrickx et al 1992). Predisposing factors in children include neurologic and immunologic disorders, diabetes, hypoparathyrosis, psoriasis, and various diseases (including parasitoses) that result in immunosuppression, i.e., measles, pneumocystosis, candidiasis (Burgess 1994;Bergman et al 1999;Patel et al 1999). Young gorillas are highly social and the fact that only juvenile animals suered from severe active mange strongly suggests the existence of factors (prior or concurrent to mite infestation) that predisposed these gorillas to scabies and allowed the progression of the disease.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The mange described in the juvenile gorilla in the present study was clinically very similar to classical crusted scabies in children (Burgess 1994;Patel et al 1999;Gladstone and Darmstadt 2000), including reports from this region of Africa (Schmeller 1998;Henderson and Nykia 1992;Heyndrickx et al 1992). Predisposing factors in children include neurologic and immunologic disorders, diabetes, hypoparathyrosis, psoriasis, and various diseases (including parasitoses) that result in immunosuppression, i.e., measles, pneumocystosis, candidiasis (Burgess 1994;Bergman et al 1999;Patel et al 1999). Young gorillas are highly social and the fact that only juvenile animals suered from severe active mange strongly suggests the existence of factors (prior or concurrent to mite infestation) that predisposed these gorillas to scabies and allowed the progression of the disease.…”
Section: Discussionsupporting
confidence: 74%
“…Prompt and adequate therapy is bene®cial and prevents the spread of these ectoparasites (Burgess 1994;Olasode and Onayemi 1998). In immunocompetent and immunocompromised children, topical therapy usually fails to cure crusted scabies (Patel et al 1999;Gladstone and Darmstadt 2000). In the present study, antiscabietic treatment with ivermectin administered by injection was successful against hyperkeratotic scabies, and no side eects occurred.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Attention has turned towards the use of oral ivermectin as a highly effective alternative treatment, [3][4][5][6][7][8][9][10] but there remains no definitive consensus on the optimal dosing regimen (including the total number of doses and interval between them) and on the need for concomitant topical therapy. 11 12 The majority of reports suggest the use of two doses (200 mg/kg each) given 2 weeks apart.…”
Section: Discussionmentioning
confidence: 99%
“…These patients were probably included in their subsequent reports. 39,40 Patel et al 41 reported on the successful use of a single oral dose of 200 lg/Ivm/kg body weight in two immunode®cient children 4 and 12 years old with CS. There are many more isolated reports of the use of Ivm in CS.…”
Section: Effect Of Ivm In Immunosuppressedmentioning
confidence: 99%